1972
DOI: 10.1002/ajpa.1330360205
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Crown‐Rump length from fetal long bones: Humerus and femur

Abstract: Lengths of the ossified diaphysis of the humerus and femur were measured in 50 fetuses ranging from 65 to 290 mm Crown-Rump length. A significant correlation was found between the diaphyseal length and the CR length. No appreciable difference was noted in diaphyseal lengths of the humerus and femur i n fetuses of 85 mm CR length or below. Various growth phases were observed. The difference i n length of the femur and humerus is due to a comparative slow growth of the humerus during the later period of prenatal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

1979
1979
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…In a study of 50 fetuses (CRL between 65 and 290 ram), Mehta and Singh (1972) suggested that measurements of the ossified regions of humerus and femur could be used to determine the CRL. Bagnall et al (1982), in a radiographic study of the growth of ossification centres in limb long bones of human fetuses from 8 to 24 weeks, observed that humeral growth appeared much more marked on the left side of the body, and suggested that some other factors, such as manual dominance, may be related to it.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study of 50 fetuses (CRL between 65 and 290 ram), Mehta and Singh (1972) suggested that measurements of the ossified regions of humerus and femur could be used to determine the CRL. Bagnall et al (1982), in a radiographic study of the growth of ossification centres in limb long bones of human fetuses from 8 to 24 weeks, observed that humeral growth appeared much more marked on the left side of the body, and suggested that some other factors, such as manual dominance, may be related to it.…”
Section: Discussionmentioning
confidence: 99%
“…Mehta and Singh (1972) concluded their investigation by suggesting that once the CRL could be estimated from the length of the ossified shafts of humerus and femur, the fetal age could be estimated with reasonable accuracy. Kelemen et al (1984) measured the length of 491 long bones derived from 193 human fetuses (developmental age from 7 to 22 weeks) and suggested a linear correlation between the fetal age (assessed by measuring the CRL) and the long bone length.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another method uses long bone measurements first to estimate fetal body size; the estimated body size is then used to estimate fetal age (Mehta and Singh, 1972;Fazekas and Kósa, 1978). Although producing a point estimate of gestational age, this method results in a compounded error (Smith, 1996).…”
mentioning
confidence: 99%
“…The total length of the femora, measured by a slide calliper under a stereomicroscope, ranged between 12.5 and 126 mm. Conceptual age was calculated by correlation with the menstrual age reported on the catalog of the collection and by morphometric parameters commonly reported in literature: biparietal diameter and/or length of the ossified shaft of long bones for the smaller samples [1,11,[12][13][14][15]. The femora (it was not possible to identify the sex of the specimens) did not show any detectable malformation.…”
mentioning
confidence: 99%